2015
DOI: 10.3892/ol.2015.3912
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole inhibits human gastric adenocarcinoma SGC-7901 cells by downregulating the expression of pyruvate kinase M2

Abstract: Abstract. The Warburg effect is important in tumor growth. The human M2 isoform of pyruvate kinase (PKM2) is a key enzyme that regulates aerobic glycolysis in tumor cells. Recent studies have demonstrated that PKM2 is a potential target for cancer therapy. The present study investigated the effects of pantoprazole (PPZ) treatment and PKM2 transfection on human gastric adenocarcinoma SGC-7901 cells in vitro. The present study revealed that PPZ inhibited the proliferation of tumor cells, induced apoptosis and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
(36 reference statements)
1
11
0
Order By: Relevance
“…In accordance with our metabolic data, the decrease in phenylalanine or increase in alanine also contributes to enhanced aerobic glycolysis in tumor cells because these amino acids might act as allosteric inhibitors to the tetramer conformations of PKM1 or PKM2 [50]. PKM2 elevation might contribute to radiation resistance or poor prognosis in patients with cervical carcinoma and oral SCC, whereas reduced PKM2 expression is associated with the inhibition of cell proliferation and EMT progression or enhanced radiation sensitivity in cancer cells [51][52][53]. These findings indicate that the detected increase in PKM2 in cervical cancer and precancerous lesions is likely associated with enhanced aerobic glycolysis and tumor growth.…”
Section: Discussionsupporting
confidence: 76%
“…In accordance with our metabolic data, the decrease in phenylalanine or increase in alanine also contributes to enhanced aerobic glycolysis in tumor cells because these amino acids might act as allosteric inhibitors to the tetramer conformations of PKM1 or PKM2 [50]. PKM2 elevation might contribute to radiation resistance or poor prognosis in patients with cervical carcinoma and oral SCC, whereas reduced PKM2 expression is associated with the inhibition of cell proliferation and EMT progression or enhanced radiation sensitivity in cancer cells [51][52][53]. These findings indicate that the detected increase in PKM2 in cervical cancer and precancerous lesions is likely associated with enhanced aerobic glycolysis and tumor growth.…”
Section: Discussionsupporting
confidence: 76%
“…PPIs substantially disrupt the acidic microenvironment and suppress phosphorylation of the extracellular signal that regulates kinase 1/2, Akt/Src kinases, and pyruvate kinase M2. Consequently, apoptosis or inhibition in cancer cell development may be induced …”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we showed that acidity represents a potent mechanism of tumor immune escape, and that PPIs increase the immune reaction against tumors [ 25 , 44 , 100 ]. Beside the direct toxic effects, PPIs were also able to inhibit mTOR signaling and other metabolic pathways in gastric carcinoma cell line, and to potentiate the antitumor effectiveness of Adriamycin in mice harboring gastric carcinoma xenografts [ 101 , 102 , 103 , 104 , 105 , 106 ]. In gastric cancer models, PPIs induced cancer stem cell depletion which passed through inhibition of proliferation, sphere formation, and 5-fluorouracil chemoresistance [ 107 ].…”
Section: V-atpase Inhibitorsmentioning
confidence: 99%